Batas Alasan Syar'i dalam Penolakan Wali Nikah: Analisis Putusan Wali ‘Adhal di Pengadilan Agama - Nazilah Maghfiroh; Fiska Silvia Raden Roro (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article examines the limits of the Sharia grounds that may justify the refusal of a marriage guardian, as well as the judge’s considerations in cases involving a ‘adhal guardian. The main issue arises because Indonesian positive law has provided a mechanism for the transfer of authority from the guardian to the judicial guardian, but has not specified the valid Sharia grounds for refusing a marriage. This study is a normative legal study employing a legislative, conceptual, and casebased approach. The analysis was conducted through a grammatical and systematic interpretation of a number of court decisions, specifically Supreme Court Decision No. 703 K/Ag/2021 and several rulings by religious courts in South Jakarta, Kendal, and Banyuwangi, serving as relevant comparative material. The research findings indicate that judges do not merely assess the existence of a guardian’s refusal but also examine the grounds for such refusal. Refusals based on subjective economic factors, custom, prestige, or personal interests are generally deemed not to be in accordance with Sharia. Conversely, refusals aimed at protecting the child and preventing harm may be deemed valid. Therefore, more measurable guidelines are required to ensure that rulings are more consistent, predictable, and guarantee legal certainty.